2021
DOI: 10.1002/prot.26152
|View full text |Cite
|
Sign up to set email alerts
|

Moving pictures: Reassessing docking experiments with a dynamic view of protein interfaces

Abstract: The modeling of protein assemblies at the atomic level remains a central issue in structural biology, as protein interactions play a key role in numerous cellular processes. This problem is traditionally addressed using docking tools, where the quality of the models is based on their similarity to a single reference experimental structure. However, using a static reference does not take into account the dynamic quality of the protein interface. Here, we used all‐atom classical Molecular Dynamics simulations to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…Let us recall here that we simulated only complexes that behave as rigid bodies, so rigid bodies do not equal static objects. As observed in recent works ( Jandova et al, 2021 ; Prévost and Sacquin-Mora, 2021 ), the protein-protein complexes visited conformations outside the high quality range of CAPRI, suggesting that docking model evaluation should take this variability into account.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Let us recall here that we simulated only complexes that behave as rigid bodies, so rigid bodies do not equal static objects. As observed in recent works ( Jandova et al, 2021 ; Prévost and Sacquin-Mora, 2021 ), the protein-protein complexes visited conformations outside the high quality range of CAPRI, suggesting that docking model evaluation should take this variability into account.…”
Section: Discussionsupporting
confidence: 59%
“…They observed higher stability of interface properties for native models, and also noticed significant changes in simulations starting from crystallographic structures in their simulations of 100 ns. In another recent work, Prévost and Sacquin-Mora performed MD simulations on docking models of various quality for three complexes submitted at the CAPRI competition and observed a category change (in terms of model quality) for more than half of the models ( Prévost and Sacquin-Mora, 2021 ). Crystallographic structures stayed in the medium quality range in their 100 ns simulations and preserved more than 50% of their native contacts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the interface loses up to 50% of its initial residue pair contacts, stabilizing to a new network of residue-residue contacts that is 86% conserved on average during the last 225 ns of the simulation ( Figure 5B , insert). Recent studies, both on RecA filaments and on heterodimers, showed that stable interfaces typically conserve 70–90% of their interaction contact network when simulated at 300 K, due to thermal movements ( Boyer et al, 2019 ; Prévost and Sacquin-Mora, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Again, native models show higher stability in almost all measured properties, including the criteria traditionally used for scoring complex models in CAPRI, namely the ligand and interface RMSDs, and the fraction of native contacts from the reference experimental structure of the protein complex. Prévost and Sacquin-Mora also questioned the relevance of the current CAPRI criteria, as they are based on a single static reference structure [ 140 ]. In their work, they ran MD simulations both on the experimental reference structure and various near-native models for three CAPRI targets (see, for example, T29 in Figure 2 a) and showed how using dynamic criteria (based on the trajectory analysis and not on a single structure) can impact the models’ ranking, as they display different stabilities over time.…”
Section: E Pur Si Muove! How Can We Relate Protein Function ...mentioning
confidence: 99%